PENGARUH RELATIONSHIP MARKETING TERHADAP CUSTOMER LOYALITY PADA PT BANK RAKYAT INDONESIA UNIT GUNUNGPATI SEMARANG - Sabtarini Kusumaningsih; Titik Rianawati (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this study is to provide empirical evidence of the influence of Relationship Marketing on Customer Loyalty on PT.Bank Rakyat Indonesia Unit Gunungpati Semarang. The analytical method used in this research is the method kuantitaitif with multiple regression testing by performing classical assumption test before getting the best research model . The variable in this study is the Customer Value , Trust, Financial Bonds as independent variables and Customer Loyalty as the dependent variable . Total population of this study was 290 respondents using simple random sampling technique was obtained 74 respondents. The results of this research are Customer Value , Trust , Financial Bonds significant effect on Customer Loyalty